2017
DOI: 10.1080/09658211.2017.1334801
|View full text |Cite
|
Sign up to set email alerts
|

The impact of depression and PTSD symptom severity on trauma memory

Abstract: Posttraumatic stress disorder (PTSD) and depression frequently co-occur following a traumatic event. Differences in the processing of autobiographical memory have been observed in both disorders in the form of overgeneralised memories and negative intrusive memories. The current study examined how symptoms of PTSD and depression influence the phenomenological characteristics of trauma memories. Undergraduate students who had experienced a traumatic event (n = 696) completed questionnaires online including meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 54 publications
1
9
0
Order By: Relevance
“…Another finding of this study was the higher mean depression score in the group of nurses with STS symptoms compared with the control group, which agrees with previous findings on the positive correlation between arousal (a dimension of STS) and depression. In addition, research suggests that secondary trauma (Lombardo & Motta, 2008), recollections of trauma (Ashbaugh et al, 2017), and stressful events (Thabet et al, 2016) have a positive correlation with depression. Nurses show STS symptoms as a result of perceiving the different symptoms experienced by their patients, and witnessing this pain and suffering on a daily basis can be a severe source of stress for them.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another finding of this study was the higher mean depression score in the group of nurses with STS symptoms compared with the control group, which agrees with previous findings on the positive correlation between arousal (a dimension of STS) and depression. In addition, research suggests that secondary trauma (Lombardo & Motta, 2008), recollections of trauma (Ashbaugh et al, 2017), and stressful events (Thabet et al, 2016) have a positive correlation with depression. Nurses show STS symptoms as a result of perceiving the different symptoms experienced by their patients, and witnessing this pain and suffering on a daily basis can be a severe source of stress for them.…”
Section: Discussionmentioning
confidence: 99%
“…A positive correlation has been reported between arousal as one of the dimensions of STS and depression (Lev-Wiesel & Amir, 2001). Studies have also demonstrated the relationship of depression with secondary trauma (Lombardo & Motta, 2008), recollections of trauma (Ashbaugh, Marinos, & Bujaki, 2017), and stressful events (Thabet, Thabet, & Vostanis, 2016). Despite the very few studies on the relationship between STS and depression, many have demonstrated the relationship between PTSD and depression (Elhai, Contractor, Palmieri, Forbes, & Richardson, 2011;Wang, Tsay, & Bond, 2005;Ying et al, 2015).…”
Section: Introductionmentioning
confidence: 96%
“…The underlying psychopathology, if present, is also important. For example, undergraduates with PTSD reported more sensory details of a traumatic event whereas undergraduates with depression recorded fewer details ( 55 ). Age also seems to matter.…”
Section: Discussionmentioning
confidence: 99%
“…Particularly impaired in veterans and auditory stimuli 15,21) The importance of emotional context 19,20) Increased attention to threat-related stimuli [22][23][24][25] Difficulty in inhibitory response from distracter 26) Memory Lack of consistency in memory loss 11,15,27) Relatively consistent impairment in language memory 27) Differences by type of trauma [27][28][29] Negative effect on episodic memory [30][31][32][33] Change of existing memory/formation of negative memory [34][35][36][37] Difficulty in memory suppression 38,39) Learning Lack of consistency in learning ability loss 11,15,18) Impaired in language learning and veterans/elderly 11,15,40) Executive function Impairment of executive function 11,15,41,42) Influence independent of depression 42) Visuospatial function Relatively small effect 11,15) Relevance to abused children 29,43) 억보다…”
mentioning
confidence: 99%